TECHNOLOGY INTEGRATION IN PRIMARY EDUCATION LESSONS - Axmedova Umidaxon Yodgorjon qizi (Western European Studies, 2025)
The article presents ideas about the use of interdisciplinary integration in the lessons of primary school students. The article presents ideas about the interrelation of technology lessons and computer science lessons.
Keywords: education; primary school students; integration